3(x+4)-(9-6x)=8

Simple and best practice solution for 3(x+4)-(9-6x)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)-(9-6x)=8 equation:


Simplifying
3(x + 4) + -1(9 + -6x) = 8

Reorder the terms:
3(4 + x) + -1(9 + -6x) = 8
(4 * 3 + x * 3) + -1(9 + -6x) = 8
(12 + 3x) + -1(9 + -6x) = 8
12 + 3x + (9 * -1 + -6x * -1) = 8
12 + 3x + (-9 + 6x) = 8

Reorder the terms:
12 + -9 + 3x + 6x = 8

Combine like terms: 12 + -9 = 3
3 + 3x + 6x = 8

Combine like terms: 3x + 6x = 9x
3 + 9x = 8

Solving
3 + 9x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 9x = 8 + -3

Combine like terms: 3 + -3 = 0
0 + 9x = 8 + -3
9x = 8 + -3

Combine like terms: 8 + -3 = 5
9x = 5

Divide each side by '9'.
x = 0.5555555556

Simplifying
x = 0.5555555556

See similar equations:

| 5=5(a+b) | | 7f-2f=4f | | 5k+1=2k+4 | | 3y-1/2=4 | | 6(y+6)=6+5y | | 7(p+3)=49 | | -8w-1+1w-11= | | 7z+1-z=3+5z+3 | | T/3+4=9 | | x+10y+30z=100 | | 4m+11=19 | | 7+4u=70 | | 4x(1-x)-2(x-1)(x+1)=2x | | 3(k-21)=18x-10+6x | | 6a=5/7 | | -2.7(r+5)+1.4r= | | 6(5m+4m+3)-2+m=(9m+8m+7)2 | | 2w-9+3(4w+1)=-2(w+1) | | -5(3y-1)+6y=3(y+1) | | 2g-4=13 | | 0.01+0.02x=0.1x-0.01 | | 3(v-5)-3=-4(-5v+8)-v | | 6z-17=25 | | 7+3/12+4-2/5*9-x | | 7/3w-2/5=-6w+5/3 | | -1/3y+7=-7/4y-4/3 | | 6(z-4)+7z-4= | | 3x-7/4=-2/3x-5/3 | | 3n+14-5n= | | Q/5-1=4 | | 2(y+4)=8y-4 | | 3u+14=8(u+8) |

Equations solver categories